The Role of Recombinant AAV in Precise Genome Editing - Bijlani, Swati; Pang, Ka Ming; Sivanandam, Venkatesh; Singh, Amanpreet; Chatterjee, Saswati (Frontiers in Genome Editing, 2022)
The replication-defective, non-pathogenic, nearly ubiquitous single-stranded adeno-associated viruses (AAVs) have gained importance since their discovery about 50 years ago. Their unique life cycle and virus-cell interactions have led to the development of recombinant AAVs as ideal genetic medicine tools that have evolved into effective commercialized gene therapies. A distinctive property of AAVs is their ability to edit the genome precisely. In contrast to all current genome editing platforms, AAV exclusively utilizes the high-fidelity homologous recombination (HR) pathway and does not require exogenous nucleases for prior cleavage of genomic DNA. Together, this leads to a highly precise editing outcome that preserves genomic integrity without incorporation of indel mutations or viral sequences at the target site while also obviating the possibility of off-target genotoxicity. The stem cell-derived AAV (AAVHSCs) were found to mediate precise and efficient HR with high on-target accuracy and at high efficiencies. AAVHSC editing occurs efficiently in post-mitotic cells and tissues in vivo. Additionally, AAV also has the advantage of an intrinsic delivery mechanism. Thus, this distinctive genome editing platform holds tremendous promise for the correction of disease-associated mutations without adding to the mutational burden. This review will focus on the unique properties of direct AAV-mediated genome editing and their potential mechanisms of action.